Computational intelligence [revised and selected papers of the international joint conference, IJCCI 2009, held in Funchal-Madeira, Portugal, October 2009] - IJCCI 2009 (2009 Funchal, Madeira Islands); Madani, Kurosh; SpringerLink (Online service). (Berlin Springer, 2011)
The present book includes a set of selected extended papers from the first International Joint Conference on Computational Intelligence (IJCCI 2009), held in Madeira, Portugal, from 5 to 7 October 2009. The conference was composed by three co-located conferences:  The International Conference on Fuzzy Computation (ICFC), the International Conference on Evolutionary Computation (ICEC),  and the International Conference on Neural Computation (ICNC). Recent progresses in scientific developments and applications in these three areas are reported in this book. IJCCI received 231 submissions, from 35 countries, in all continents. After a double blind paper review performed by the Program Committee, only 21 submissions were accepted as full papers and thus selected for oral presentation, leading to a full paper acceptance ratio of 9%. Additional papers were accepted as short papers and posters. A further selection was made after the Conference, based also on the assessment of presentation quality and audience interest, so that this book includes the extended and revised versions of the very best papers of IJCCI 2009. Commitment to high quality standards is a major concern of IJCCI that will be maintained in the next editions, considering not only the stringent paper acceptance ratios but also the quality of the program committee, keynote lectures, participation level and logistics.
Part I: Fuzzy Computation -- Part II: Evolutionary Computation -- Part III: Neural Computation.
Subtitle from cover.
Electronic reproduction.
Keywords: Computational intelligence -- Congresses; Electronic books